Current forest-related discourses - Pülzl, Helga (2024)
Discourses about forests matter as they mediate or shape action. Chapter 4 presents an updateto the work of Arts et al. (2010), which used a longitudinal analysis of global forest 1 (-related)discourses and interrelated meta- and regulatory discourses and their prevalence over time takestock of the discursive shifts that emerge from the literature. This is based on a literature searchin Google Scholar, Scopus, and ISI Web of Science for the time from January 2011 to June 2023. Theresults were discussed with experts in the field to understand whether: i) important themes weremissing, and ii) discursive dynamics were misrepresented or misinterpreted. In addition, mainframing devices that have recently appeared were identified.The analysis found that a ´climatization´ of the environmental meta-discourse clearly has takenplace, and has had an impact on how forests are problematized and understood to provide climatesolutions. It identified also a refurbished discourse on ‘ecological modernisation’ with a neoliberaltwist, and several of growth-based discourses that stretch from de-growth to pro-growth, as well astransition discourses that centre around civic environmentalism and justice. Regulatory discourseswere found to not have changed considerably, but new modes of governance based on markets havebecome more common. New and refurbished forest-related discourses were also identified alongseveral framings that impact forests, such as seeing forests as carbon sinks, ecosystem serviceproviders, landscape managers, and suppliers of nature-based solutions in actual political debates.Mechanisms of power are particularly pronounced in procedures of exclusion. Knowing forestsand giving meaning to forest-related activities steers the way we see and use forests. Therefore, thechapter analyses results around frames of ‘constantly better knowledge’ about forests, the com-modification of forests into ‘tradable entities’, as well as silences (i.e., not addressing certain aspectsof forests). These frames are seen as forms of power expression. The Chapter concludes that, whilethe academic literature and debates mostly reflect current dynamics in decision-making, this anal-ysis shows that there is an ongoing polarization between different actor positions, which is likely toincrease as discourses drift apart or confront each other. Therefore, finding common positions andcompromise could become more complex and difficult in the future.